Predicting antimicrobial resistance of bacterial pathogens using time series analysis - Kim, Jeonghoon; Rupasinghe, Ruwini; Halev, Avishai; Huang, Chao; Rezaei, Shahbaz; Clavijo, Maria J.; Robbins, Rebecca C.; Martínez-López, Beatriz; Liu, Xin (Frontiers in Microbiology, 2023)
Antimicrobial resistance (AMR) is arguably one of the major health and economic challenges in our society. A key aspect of tackling AMR is rapid and accurate detection of the emergence and spread of AMR in food animal production, which requires routine AMR surveillance. However, AMR detection can be expensive and time-consuming considering the growth rate of the bacteria and the most commonly used analytical procedures, such as Minimum Inhibitory Concentration (MIC) testing. To mitigate this issue, we utilized machine learning to predict the future AMR burden of bacterial pathogens. We collected pathogen and antimicrobial data from >600 farms in the United States from 2010 to 2021 to generate AMR time series data. Our prediction focused on five bacterial pathogens Escherichia coli, Streptococcus suis, Salmonella sp., Pasteurella multocida, and Bordetella bronchiseptica). We found that Seasonal Auto-Regressive Integrated Moving Average (SARIMA) outperformed five baselines, including Auto-Regressive Moving Average (ARMA) and Auto-Regressive Integrated Moving Average (ARIMA). We hope this work provides valuable tools to predict the AMR burden not only of the pathogens assessed in this study but also of other bacterial pathogens.